Enhancing Customer Loyalty in Traveloka: Examining the Roles of E-Service Quality, Perceived Price, Customer Satisfaction, and Trust - Anton Robin Simamora; Gunadi, Willy (Universitas Muhammadiyah Pontianak, 2026)
This study examines factors influencing customer loyalty among Traveloka users in Greater Jakarta. It investigates the effects of e-service quality and perceived price on customer loyalty, with customer satisfaction and trust as mediating variables. Data were collected from 203 Traveloka users who had made transactions within the past 12 months and analysed using SEM-PLS. The results show that e-service quality and perceived price significantly affect customer satisfaction, trust, and loyalty. Customer satisfaction also significantly affects trust and loyalty, while customer trust has no significant effect on loyalty. The findings highlight the importance of service quality, price perception, and satisfaction in strengthening OTA customer loyalty. keywords: E-Service Quality; Perceived Price; Customer Satisfaction; Trust; Customer Loyalty; Online Travel Agency; E-Commerce; Digital Reservation